校長領導對教師學習領導的影響：檢視信任關係與學業強調的調節作用 The Effect of Principal Leadership on Teacher Leadership for Learning: How Trust and Academic Emphasis Moderate? - 陳文彥 Wen-Yan Chen; 潘慧玲 Hui-Ling Wendy Pan (National Taiwan Normal University, 2019)
在講求分享管理的學校經營中，教師學習領導十分重要，惟過去甚少有研究觸及其如何受到校長領導之影響。為了檢視校長對教師發揮促進學習的領導具有何等效應，特別是此效應是否會因學校裡的信任關係及重視學業程度而有所差異，本研究以國中教師為對象，運用問卷調查法進行探討，共回收 1,340 份有效問卷，研究結果獲得以下重要發現：一、國中教師對於本研究所探討的四個焦點（校長領導、教師學習領導、教師對校長的信任關係及學校學業強調），知覺程度均達中高標。不過，教師學習領導之得分顯著高於其他三者；得分次高者為信任關係。二、教師背景變項對其知覺程度之影響，系統性達顯著水準者為教師兼任行政與否。三、校長領導對於教師學習領導的影響效果，受到信任關係與學業強調的調節；信任關係對於校長領導的影響力具有加乘作用，而高學業強調則對校長領導之影響力產生壓抑效果。有關學業強調之正向功能，其強度不若西方脈絡中所呈現的，適足彰顯本研究發現具有的文化意涵。 Teacher leadership for learning is significant for school management in the context of shared governance, while there is scarce literature regarding how it is influenced by principal leadership. To examine principal effect on teacher leadership and how the effect is moderated by teacher trust in principal and school academic emphasis, the study administered a survey to 1,340 junior high school teachers in Taiwan. Important findings are concluded as follows: (1) Teacher perceptions of principal leadership, teacher leadership for learning, teacher trust in principal and school academic emphasis all reached moderately high level. Teacher leadership for learning was ranked as the top, followed by teacher trust in principal. (2) Among the demographic variables, teachers with formal administrative post or not was found to exert significant influence on the aforementioned teacher perceptions. (3) The effect of principal leadership on teacher leadership for learning was moderated by teacher trust and academic emphasis. In other words, principal effect on teacher leadership was more vivid in schools where teachers had higher degree of trust in principals, and less evidently in schools with stronger extent of academic emphasis. The study features itself with cultural implication for its presenting weaker significance of academic emphasis than that found in the western context.